Perancangan Kampanye Sebagai Pendukung Program Satuan Tugas Pencegahan Dan Penanganan Kekerasan Seksual Di Universitas Ichsan Gorontalo (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Sexual violence in the university environment is a serious issue that requires special attention. Ichsan University of Gorontalo, through the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) program, strives to create a safe campus environment free from sexual violence. This study aims to design an effective visual communication campaign to support the Satgas PPKS program. The campaign was designed using the Design Thinking approach, which focuses on understanding the needs of the target audience and producing innovative visual solutions. This study uses a qualitative method with data collection through interviews, focus group discussions (FGD), observation, and documentation studies. The media designed include social media content, posters, and infographics. The research process includes five main stages, namely empathy, problem definition, ideation, prototype, and testing.